Use of left atrial appendage as an autologous tissue source for epicardial micrograft transplantation during LVAD implantation - Schmitto, Jan D.; Kuuva, Aleksi; Kronström, Kai; Hanke, Jasmin S.; Kankuri, Esko (Frontiers in Cardiovascular Medicine, 2023)
We report here the first clinical use of the left atrial appendage (LAA) for epicardial micrograft transplantation during left ventricular assist device (LVAD) implantation. Previously, a sample from the right atrial appendage (RAA) has been available for processing and administering micrograft therapy in cardiac surgery. Both LAA and RAA are rich sources of various types of myocardial cells and are capable of providing both paracrine and cellular support to the failing myocardium. The surgical approach of LAA micrografting facilitates epicardial micrograft therapy dose escalation and treatment of larger myocardial areas than done previously. Moreover, as collection of treated vs. untreated tissues from the recipient heart is possible following LVAD implantation at the time of heart transplantation, the evaluation of the therapy's mechanism of action can be further deciphered at cellular and molecular levels. This LAA modification of the epicardial micrografting technique has the overall potential to facilitate the adoption of cardiac cell therapy during heart surgery.